The effect of the Maternal Care Manual of the Perinatal Education Programme on the Attitude of Mid wives towards their work - GB Theron (AOSIS, 1999)
In this study the changes in attitude of midwives towards their work following completion of the Maternal Care Manual of the Perinatal Education Programme (PEP), were determined.